Does local dynamic stability of kayak paddling technique affect the sports performance? A pilot study. Issue 4 (21st April 2018) - Hamacher, Daniel; Krebs, Tobias; Meyer, Guido; Zech, Astrid
ABSTRACT: During competition, kayak athletes must optimally adapt to environmental factors (e.g. wind, waves) to achieve peak performance. However, the ability to adapt to such perturbations has never been assessed in kayak paddling. Therefore, the aim of the current study was to evaluate the local dynamic stability in sports technique of youth sprint kayak athletes. In a cross-sectional study, 14 healthy male athletes were recruited from an elite youth sprint kayak squad. During an incremental kayak ergometer test, mean power, heart rates and local dynamic technique stability of hands, arms, trunk and paddle were registered and the association with the athletes 2000 m free-water times were estimated using mixed models. The 2000 m free-water performance significantly predicted the paddles ( p = .037) local dynamic stability whereas no association was found for the trunk or the upper extremity kinematics. In conclusion, kayak athletes with high-performance capability over 2000 m paddling depict high local dynamic technique stability. This emphasizes the importance of a stable technique for advanced kayak skills, especially regarding paddling movements.